PENANAMAN NILAI AGAMA HINDU PADA ANAK USIA DINI DI TK PELANGI DHARMA NUSANTARA - Suadnyana, Ida Bagus Eka (Kumarottama: Jurnal Pendidikan Anak Usia Dini, 2021)
Early age is the right time to develop children's potential and intelligence. To avoid developing the potential of children at random, it is necessary to instill Hindu religious values ​​from an early age. Seeing the learning pattern that is contrary to the provisions of the minister of education which prohibits calistung in early childhood, the researchers are interested in researching this at Pelangi Dharma Nusantara Kindergarten. The theory used to solve the research problem is the humanistic theory and the behavioristic theory. This research is in the form of qualitative research. Data were collected by three techniques, namely observation, interview and document study. After the data is collected, the data is analyzed by data reduction, data presentation, and drawing conclusions. Based on the analysis, the following conclusions were obtained: (1) The methods used in the activities of inculcating Hindu religious values ​​in early childhood at Pelangi Dharma Nusantara Kindergarten are methods of playing, habituation, field trips and exemplary, (2) Efforts made by teachers in overcoming problems instilling Hindu religious values ​​in early childhood at Pelangi Dharma Nusantara Kindergarten is by providing supervision, understanding, introducing noble behavior and counseling to parents of students